Prevalence of Emergence Delirium and Associated Factors among Older Patients Who Underwent Elective Surgery: A Multicenter Observational Study - Gezahegn Tesfaye Mekonin; Megersa Kelbesa Olika; Mitiku Birhanu Wedajo; Ashanafi Tolasa Badada; Abebe Dukessa Dubiwak; Tajera Tageza Ilala; Mamo Nigatu Gebre (Anesthesiology Research and Practice)
Background. Emergence delirium is a common and serious postoperative complication in older surgical patients. It occurs at any time in the perioperative period, during or immediately following emergence from general anesthesia. Unfortunately, it is highly associated with postoperative complications such as a decrease in functional capacity, prolonged hospital stay, an increase in health care costs, and morbidity and mortality. The goal of this study was to determine the prevalence of emergence delirium and associated factors among older patients who underwent elective surgery in the teaching hospitals of Ethiopia at the postanesthesia care unit in 2021. Methods. A multicenter prospective observational study was conducted at the postanesthetic care unit in the four teaching hospitals of Ethiopia. Older surgical patients admitted to the postanesthesia care unit who underwent elective surgery in the four teaching hospitals of Ethiopia were selected by using simple random sampling. Pretested structured questionnaire was used to collect data. Data were entered into EpiData (version 4.6) and exported to the SPSS (version 25.0). Binary logistic regression was used to identify factors independently associated with the emergence delirium. Results. Out of 384 older patients included in the study, the prevalence of emergence delirium was 27.6%. Preoperative low hemoglobin levels (AOR: 2.0, 95% CI; 1.77–3.46), opioid (AOR: 8.0, 95% CI; 3.22–27.8), anticholinergic premedications (AOR: 8.5, 95% CI; 6.85–17.35), and postoperative pain (AOR: 3.10, 95 CI; 2.07–9.84) at PACU were independently associated with emergence delirium. Conclusion. The prevalence of emergence delirium was high among older patients who underwent elective surgery. Opioid and anticholinergic premedication, low preoperative hemoglobin, and the presence of postoperative pain were independently associated with the emergence delirium. Adequate preoperative optimization and postoperative analgesia may reduce the prevalence of emergence delirium.